Rhodium-Catalyzed Atroposelective C–H Arylation: Efficient Synthesis of Axially Chiral Heterobiaryls - Wang, Qiang; Cai, Zhong-Jian; Liu, Chen-Xu; Gu, Qing; You, Shu-Li (Journal of the American Chemical Society, 2019)
Rhodium(I)-catalyzed atroposelective C–H arylation of heterobiaryls was presented. In the presence of a Rh catalyst derived from [Rh(C2H4)2Cl]2 and a TADDOL-derived monodentate phosphonite, with 2-pyridine, 2-isoquinoline and their analogs as directing groups, a series of axially chiral heterobiaryls were obtained in excellent yields and enantioselectivities (up to 99% yield, 97% ee) via C–H direct functionalization reaction. The products obtained from this method provide a platform for the synthesis of axially chiral biaryl ligands and catalysts. As a demonstration, a chiral N-oxide synthesized from the product in one step could act as an efficient catalyst for asymmetric allylation of benzaldehyde with allyltrichlorosilane, leading to homoallyl alcohol with excellent enantiocontrol.